Relative associations of abdominal and thigh compositions with cardiometabolic diseases in African Caribbean men - Curtis Tilves (Wiley, 2021)
Abstract Background Regional body compositions are differentially associated with cardiometabolic risk factors. Simultaneous inclusion of both upper and lower body composition predictors in models is not often done, and studies which do include both measures (1) tend to exclude some tissue(s) of potential metabolic relevance, and (2) have used study populations with underrepresentation of individuals with African ancestries. Further, most body composition analyses do not employ compositional data analytic approaches, which may result in spurious associations. Objective The objective of this analysis was to assess associations of abdominal and thigh adipose (AT) and muscle tissues with hypertension and type 2 diabetes using compositional data analytic methods. Research Design and Methods This cross‐sectional analysis included 610 African Caribbean men (median age: 62 years; mean BMI: 27.8 kg/m2). Abdominal (three components: subcutaneous [ASAT] and visceral [VAT] AT, ‘other’ abdominal tissue) and mid‐thigh (four components: subcutaneous and intermuscular AT, muscle, bone) compositions were measured by computed tomography; additive log ratio transformations were applied to each composition. Regression models were used to simultaneously assess associations of abdominal and thigh component ratios with continuous risk factors (blood pressures, fasting glucose and insulin, HOMA‐IR) and disease categories. Results A two‐fold increase in ASAT:‘Other’ ratio was associated with higher continuous risk factors and with odds of being in a higher hypertension (OR: 1.77, 95%CI: 1.10–2.84) or diabetes (OR: 1.81, 95%CI: 1.06–3.10) category. A two‐fold increased VAT ratio was only associated with higher log‐insulin and log‐HOMA‐IR (β = 0.10, p < 0.05 for both), while a two‐fold increased thigh muscle:bone ratio was associated with a lower diabetes category (OR: 0.37, 95%CI: 0.14–1.01). Conclusions These findings support ASAT as a significant driver of cardiometabolic disease in African Ancestry populations, independent of other abdominal and thigh tissues.